2011
DOI: 10.1007/s11764-011-0209-3
|View full text |Cite
|
Sign up to set email alerts
|

“Weaving Balance into Life”: Development and cultural adaptation of a cancer symptom management toolkit for Southwest American Indians

Abstract: Introduction Self-management of cancer symptoms has the potential to decrease the suffering of cancer survivors while improving their health and quality of life. For many racial/ethnic groups, culturally appropriate self-management instruction is not readily available. This paper reports on the first symptom management toolkit developed for American Indian cancer survivors. Methods Part of a larger research study, a three-phase project tested a cancer symptom self-management toolkit to be responsive to the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 13 publications
(11 reference statements)
1
41
1
Order By: Relevance
“…Professionals were valued for their expert knowledge. Patients needed information from an expert about diagnosis, symptoms, treatment options, side‐effects and possible interaction effects and instruction on alleviating symptoms themselves . Support should be available shortly after symptoms arise or when there are problems with medication .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Professionals were valued for their expert knowledge. Patients needed information from an expert about diagnosis, symptoms, treatment options, side‐effects and possible interaction effects and instruction on alleviating symptoms themselves . Support should be available shortly after symptoms arise or when there are problems with medication .…”
Section: Resultsmentioning
confidence: 99%
“…Support should be available shortly after symptoms arise or when there are problems with medication . In some studies, patients appreciated information about spiritual matters and complementary therapy . Professionals also helped evaluate internet information, a role attributed to relatives in another study .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[323334] While the results from these programs were supportive to cancer patient self-management, the development of such program and validation of usefulness and sustainability for cancer patients who have language and cultural barriers are still limited. [3536]…”
Section: Discussionmentioning
confidence: 99%
“…However, cultural preferences may still be an important component of health communication. A recent study incorporating 13 focus groups made up of American Indian cancer survivors from the Southwest U.S. found that participants preferred educational materials tailored to their belief and culture [26]. …”
Section: Discussionmentioning
confidence: 99%